Cho hai đa thức A(x) = 2 x^ 3 + 2 x^2 + 3 x – x + 3 – x = 4 x^ 2 – 6 x^ 2 + 2 x – x + 4;p(x)= 4 x^ 3 – 6 x ^2 + 2 x -x + 4

Question

Cho hai đa thức A(x) = 2 x^ 3 + 2 x^2 + 3 x – x + 3 – x = 4 x^ 2 – 6 x^ 2 + 2 x – x + 4;p(x)= 4 x^ 3 – 6 x ^2 + 2 x -x + 4

in progress 0
Mary 1 tháng 2021-08-12T02:56:00+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-08-12T02:57:21+00:00

    Đáp án:

    \(b)A\left( x \right) + B\left( x \right) = 6{x^3} – 4{x^2} + 3x + 11\) 

    Giải thích các bước giải:

    \(\begin{array}{l}
    a)A\left( x \right) = 2{x^3} + 2{x^2} + 3x – x + 3 – x + 4{x^2} – 6{x^2} + 2x – x + 4\\
     = 2{x^3} + \left( {2 + 4 – 6} \right){x^2} + \left( {3 – 1 – 1 + 2 – 1} \right)x + 7\\
     = 2{x^3} + 2x + 7\\
    B\left( x \right) = 4{x^3} – 6{x^2} + 2x – x + 4\\
     = 4{x^3} – 6{x^2} + x + 4\\
    b)A\left( x \right) + B\left( x \right) = 2{x^3} + 2x + 7 + 4{x^3} – 6{x^2} + x + 4\\
     = 6{x^3} – 4{x^2} + 3x + 11
    \end{array}\)

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )